Pengaruh Pengetahuan Wajib Pajak, Kesadaran Wajib Pajak, danSanksi Pajak terhadap Kepatuhan Wajib Pajak pada KantorPelayanan Pajak Pratama Jakarta Cengkareng - Edo Setiawan; Akhmad Hidayat Rahadian (Jurnal Pajak Vokasi (JUPASI), 2026)
The background of this thesis discusses the Influence of Taxpayer Knowledge, Taxpayer Awareness, and Tax Sanctions together toward Taxpayer Complience at the Jakarta Cengkareng Pratama Tax Service Office. The research method used is quantitative. Data processing techniques use simple and multiple linear regression. The results of statistical analysis show that there is a positive and significant influence of Taxpayer Knowledge toward Compliance at the Jakarta Cengkareng Tax Office with a large influence of 28.1%. If Taxpayer Knowledge is increased, it will increase Taxpayer Compliance at the Jakarta Cengkareng Tax Office. There is a positive and significant influence of Taxpayer Awareness toward Compliance at the Jakarta Cengkareng Tax Office. The large influence is 53.2%. If taxpayer awareness is increased, it will increase Taxpayer Compliance at KPP Jakarta Cengkareng. There is a positive and significant influence of Tax Sanctions toward Compliance at KPP Jakarta Cengkareng. The magnitude of the influence is 98.6%. If tax sanctions are increased, it will increase Taxpayer Compliance at KPP Jakarta Cengkareng. There is a positive and significant influence of Taxpayer Knowledge, Taxpayer Awareness and Tax Sanctions together toward Compliance at KPP Jakarta Cengkareng. Stated by the F count value (2485.547) > F table (2.70). This means that H0 is rejected and the consequence is H3 is accepted, then the consequence is Taxpayer Knowledge, Taxpayer Awareness and Tax Sanctions toward Compliance at KPP Jakarta Cengkareng. With an Adjusted R Square influence of 98.7% and the remaining 1.3% is influenced by other factors not studied. Keywords: Taxpayer Knowledge; Taxpayer Awareness; Tax Sanctions; Taxpayer Complience;